2002
DOI: 10.1097/00005373-200202000-00012
|View full text |Cite
|
Sign up to set email alerts
|

All Patients with Truncal Gunshot Wounds Deserve Trauma Team Activation

Abstract: Patients with GSWT often require high-level care, even when physiologic TTA criteria are absent on admission. Gunshot wound to the trunk should be an independent criterion for TTA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 21 publications
1
9
0
1
Order By: Relevance
“…Traditional criteria for the activation of trauma teams for penetrating trauma have focused on triage vital signs 1. Haemorrhage is responsible for about 30%–40% of mortality in trauma patients 2.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional criteria for the activation of trauma teams for penetrating trauma have focused on triage vital signs 1. Haemorrhage is responsible for about 30%–40% of mortality in trauma patients 2.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of penetrating trauma in the United States has fortunately diminished and with it has diminished the need for the general surgeon to take the patient to the OR. 16 Rather the focus of operative trauma has increased for the orthopedic and neurosurgeons and to some degree the maxillofacial surgeons. This change provides an opportunity to further refine the trauma system by incorporating the ED as an integral member and to entrust to those team members the initial management of some traumatic injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Penetrating trauma to the trunk may initially be associated with deceptively normal vital signs despite grave injury (Sava et al, 2002). Sava et al (2002) working in a Level 1 trauma center in California looked at a series of over 4198 patients who had received gun shot wounds to the trunk. They observed that 6% of these did not achieve traditional trauma team activation criteria.…”
Section: Acute Managementmentioning
confidence: 99%